Agricultural growth, urbanization, and poverty reduction - Dorosh, Paul A.; Thurlow, James (International Food Policy Research Institute, 2021)
Rapid urbanization is a defining feature of low-income countries, even as rural populations continue to grow. Greater attention should therefore be paid to the spatial dimensions and urban drivers of agricultural transformation. Unfortunately, agricultural and urban policies are usually developed in isolation from each other and are often viewed as being in competition. This perceived competition between sectors has led many countries to adopt policies aimed at curbing internal migration or redirecting scarce public resources toward agriculture. However, urban populations are growing rapidly in low-income countries and a large share of urban residents are poor and live in slums. Even maintaining urban investments at current levels will be insufficient and could become a constraint to national development, including efforts to transform agriculture-food systems.